Executive Committee Minutes 2015-05-07 - Academic Senate:::::::::
Agenda – Approved. Minutes of April 23 – delayed. Chair Report. President Report. Provost Report. Statewide Senator Report. Vice Chair Report. Vice President of Administration and Finance Report. French Language for Wine Business certificate approved for Senate consent calendar. Vice President of Student Affairs Report. Revision to the Biochemistry BS program approved for Senate consent calendar. Quorum for summer Executive Committee approved. FSAC recommendation regarding staff input on Department Chair. EPC Report. Reassigned time for '15 – '16 with addition of EPC proposal – approved. FSAC Report. Associated Students Report. Ex Com representative to SEC Report. Senate agenda approved.